Mammoths at the Gates - Vo, Nghi (Vo, Nghi. Singing Hills cycle., 2023)
The wandering Cleric Chih returns home to the Singing Hills Abbey for the first time in almost three years, to be met with both joy and sorrow. Their mentor, Cleric Thien, has died, and rests among the archivists and storytellers of the storied abbey. But not everyone is prepared to leave them to their rest. Because Cleric Thien was once the patriarch of Coh clan of Northern Bell Pass--and now their granddaughters have arrived on the backs of royal mammoths, demanding their grandfather's body for burial. Chih must somehow balance honoring their mentor's chosen life while keeping the sisters from the north from storming the gates and destroying the history the clerics have worked so hard to preserve. But as Chih and their neixin Almost Brilliant navigate the looming crisis, Myriad Virtues, Cleric Thien's own beloved hoopoe companion, grieves her loss as only a being with perfect memory can, and her sorrow may be more powerful than anyone could anticipate. . .